Metal distribution and disorder in the crystal structure of [NH2Et2][Cr7MF8(tBuCO2)16] wheel molecules for M = Mn, Fe, Co, Ni, Cu, Zn and Cd. Issue 6 (7th November 2014) - Larsen, Finn Krebs; Overgaard, Jacob; Christensen, Mogens; McIntyre, Garry James; Timco, Grigore; Winpenny, Richard E. P.
<x xml:space="preserve">Abstract</x> The homometallic wheel compound [Cr8F8(O2CCMe3)16] formed with fluorine and pivalic acid ligands can be modified by introducing in the synthesis process a divalent cation M capable of octahedral coordination instead of one of the trivalent Cr centres in the ring. Heterometallic mono‐anionic species [Cr7MF8(O2CCMe3)16]− can form diethylammonium salts and be crystallized from ethylacetate solution as compounds with the general formula [NH2Et2][Cr7MF8(tBuCO2)16][C4H8O2]0.5 for M = Mn, Fe, Co, Ni, Cu, Zn and Cd. Their structures are isomorphous, belonging to the space group P21/c. The study has determined the degree of order for the individual M heterometal over the possible metal positions of the ring in the crystal structure by modelling based on X‐ray diffraction data. The model took into account disorder in tert‐butyl groups of the pivalate ligands and in the position and orientation of the ethylacetate solvent molecule. The heterometal turned out to be partly ordered in the crystal structure.